Perceiving clinical evidence. - Cox K (Medical Education, 2002)
Background This paper demystifies clinical perception by explaining its mechanisms, using insights from neuroscience and evolutionary biology. Clinical diagnosis begins with rapid recognition using our imaging, perceptual (but non-verbal) brain, followed by guided search using our slower, verbal, reasoning brain. Experiential cognition can be (more or less) achieved by integrating these two ways of knowing. Perceptual expertise requires alertness and persistence to ensure clinical accuracy. Each clinician, as a self-aware participant-observer (SAPO) keeping track of what they're thinking 'as it happens', can study their perceptual accuracy, pattern matching, interpretation, motivation and judgement.